AI AND DIGITAL COMMUNICATION INTEGRATION IN LEARNING: THE GOVERNMENT'S ADAPTIVE STRATEGY FOR CITIZEN RESPONSIVE EDUCATION IN THE DIGITAL AGE - Utami, Pri (GoAcademica Research dan Publishing, 2023)
The use of artificial intelligence (AI) and digital communication has changed the educational landscape, bringing new challenges and opportunities to the learning process. However, this technological integration requires a wise approach to maintaining a balance between technology and human interaction. This study aims to analyze how the use of AI technology and digital communication can shape the dynamics of modern education, explore potentials, challenges, as well as emerging social and ethical implications. This study adopts a descriptive qualitative approach, with data obtained from previous studies that are relevant to the role of AI and digital communication in the educational context. Through data analysis, this study identified best practices in using AI technology, challenges in integrating it, and its impact on the roles of teachers and students. The results of this study underscore the need for a holistic approach in the use of technology in education, by preserving the essence of human education and designing sustainable strategies to respond to technological changes. By deeply understanding the implications of using AI technology and digital communication in education, we can form a solid foundation for facing challenges and opportunities in digital era education.